2019
DOI: 10.1109/access.2019.2894500
|View full text |Cite
|
Sign up to set email alerts
|

An Image Processing Approach to Measuring the Sphericity and Roundness of Fracturing Proppants

Abstract: Before being applied in oil fields, it is necessary to evaluate the quality of the fracturing proppants, for which sphericity and roundness are the two important parameters. In this paper, we propose a new approach to the sphericity and roundness measurement of proppants based on an image processing method. First, the OTSU method is introduced to binarize proppant image, and the statistical analysis is performed to divide the image into proppant regions and non-proppant regions. Second, after filling small hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For proppant extraction, it is found that the threshold method, such as Otsu method [30], is effective to some extent, and From the proppant extraction experiments both for proppants of quartz sand and proppants of ceramics, the results of the Otsu method or level set method contain many regions that do not belong to proppants, and the fuzzy connectedness method has a better performance. Although the result of the fuzzy connectedness method is worse than that of the former algorithm [24], the reason is that the algorithm [24] uses the subtraction method of two images. The first image is without proppants and the second one is with proppants, meanwhile the placement plane should be fixed during image acquisition.…”
Section: A Proppant Extraction Experimentsmentioning
confidence: 94%
See 4 more Smart Citations
“…For proppant extraction, it is found that the threshold method, such as Otsu method [30], is effective to some extent, and From the proppant extraction experiments both for proppants of quartz sand and proppants of ceramics, the results of the Otsu method or level set method contain many regions that do not belong to proppants, and the fuzzy connectedness method has a better performance. Although the result of the fuzzy connectedness method is worse than that of the former algorithm [24], the reason is that the algorithm [24] uses the subtraction method of two images. The first image is without proppants and the second one is with proppants, meanwhile the placement plane should be fixed during image acquisition.…”
Section: A Proppant Extraction Experimentsmentioning
confidence: 94%
“…The comparison experimental results of different proppants with different methods include manual measurement method, Pei's method [16], the method [24] proposed by the author in 2019 named Lyu2019, Zheng's method [21], [22](based on fuzzy connectedness extraction result and S WL is selected as the sphericity) and the proposed method in this paper.…”
Section: B Sphericity and Roundness Determination Experimentsmentioning
confidence: 99%
See 3 more Smart Citations